On-demand transfer of trapped photons on a chip - Konoike, Ryotaro (Sci Adv, 2016)
Photonic crystal nanocavities, which have modal volumes of the order of a cubic wavelength in the material, are of great interest as flexible platforms for manipulating photons. Recent developments in ultra-high quality factor nanocavities with long photon lifetimes have encouraged us to develop an ultra-compact and flexible photon manipulation technology where photons are trapped in networks of such nanocavities. The most fundamental requirement is the on-demand transfer of photons to and from the trapped states of arbitrary nanocavities. We experimentally demonstrate photon transfer between two nearly resonant nanocavities at arbitrary positions on a chip, triggered by the irradiation of a third nonresonant nanocavity using an optical control pulse. We obtain a high transfer efficiency of ~90% with a photon lifetime of ~200 ps.